Organized essays - Bodden, Valerie (Mankato, MN : Creative Education, 2011)
"An introduction to the ways that writers compose well-structured essays. Excerpts and analysis help to explain the importance of perspective and research in this nonfiction form"--Provided by publisher.
Essays then and now -- Forms and functions -- Setting up the structure -- Design and development -- Saying it with style -- Think like an essayist.
Includes bibliographical references (p. 47) and index.
Keywords: Essay -- Authorship -- Juvenile literature; Essay -- Authorship